SIRT1/PGC-1α/PPAR-γ Correlate With Hypoxia-Induced Chemoresistance in Non-Small Cell Lung Cancer - Xu, Rui; Luo, Xin; Ye, Xuan; Li, Huan; Liu, Hongyue; Du, Qiong; Zhai, Qing (Frontiers in Oncology, 2021)
Resistance is the major cause of treatment failure and disease progression in non-small cell lung cancer (NSCLC). There is evidence that hypoxia is a key microenvironmental stress associated with acquired resistance to cisplatin and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in solid NSCLCs. Numerous studies have contributed to delineating the mechanisms underlying drug resistance in NSCLC; nevertheless, the mechanisms involved in the resistance associated with hypoxia-induced molecular metabolic adaptations in the microenvironment of NSCLC remain unclear. Studies have highlighted the importance of posttranslational regulation of molecular mediators in the control of mitochondrial function in response to hypoxia-induced metabolic adaptations. Hypoxia can upregulate the expression of sirtuin 1 (SIRT1) in a hypoxia-inducible factor (HIF)-dependent manner. SIRT1 is a stress-dependent metabolic sensor that deacetylates transcription factors such as HIF1α, peroxisome proliferator-activated receptor gamma (PPAR-γ), and PPAR-gamma coactivator 1-alpha (PGC-1α) to affect mitochondrial function and biogenesis, which has a role in hypoxia-induced chemoresistance in NSCLC. The objective of this review is to delineate a possible SIRT1/PGC-1α/PPAR-γ signaling-related molecular metabolic mechanism underlying hypoxia-induced chemotherapy resistance in the NSCLC microenvironment. Targeting hypoxia-related metabolic adaptation may be an attractive therapeutic strategy for overcoming chemoresistance in NSCLC.